Guest-oriented non-fullerene acceptors for ternary organic solar cells with over 16.0% and 22.7% efficiencies under one-sun and indoor light. (September 2020) - Cho, Yongjoon; Kumari, Tanya; Jeong, Seonghun; Lee, Sang Myeon; Jeong, Mingyu; Lee, Byongkyu; Oh, Jiyeon; Zhang, Youdi; Huang, Bin; Chen, Lie; Yang, Changduk
Abstract: Given that the ring-fusion strategy can effectively tail the electrical, optical, and structural properties of π-conjugated materials, we have herein developed Y-series non-fullerene acceptors with a dual acceptor–donor–dual acceptor-type structure, bearing non-fused bare bithiophene (Y–Th2), hexagonal ring-fused bithiophene (Y-BDT), or pentagonal ring-fused bithiophene (Y-CDT) central donor units. Several characterization techniques were applied to perform a comparative investigation of their optical and physical properties and frontier energy levels with respect to the different ring-fusion of the central units. Moreover, for the cascade energy level alignment, the synthesized acceptors were employed as a third component in the PM6:Y6 that served as a binary host platform. The introduction of the optimal amount of Y–Th2 or Y-BDT into the host system improved the device performance. Specifically, Y–Th2 exhibited the best power conversion efficiency (PCE) (16.01%) along with improved photovoltaic parameters, whereas the addition of Y-CDT impaired the PCE. Moreover, the optimized Y–Th2-based ternary organic solar cell achieved a PCE of 22.72% under indoor illumination at 1000 lux. Thus, the in-depth structural, morphological, and electrical analyses not only established a structure–property correlation, but also provided better design criteria for the guest-oriented non-fullerene acceptors for ternary photovoltaic applications, especially for Y6-containing systems. Graphical abstract: Image 1 Highlights: Ring-fusion strategy effectively tunes the electrical, optical, and structural properties of conjugated materials. The guest-oriented non-fullerene acceptors with a dual acceptor–donor–dual acceptor-type structures are synthesized. The structures contain non-fused, hexagonal ring-fused, or pentagonal ring-fused bithiophene central donor units. The cascade energy level alignment and complementary absorption improve the photovoltaic properties of ternary solar cells. High efficiencies of 16.01% and 22.72% are achieved under one-sun and indoor light, respectively.